1985
DOI: 10.1021/bi00334a006
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of pH-dependent fusion between influenza virus and liposomes

Abstract: The pH-dependent fusion between influenza virus and liposomes (large unilamellar vesicles) has been investigated as a model for the fusion step in the infectious entry of the virus into cells. Fusion was monitored continuously, with a fluorescence assay based on resonance energy transfer (RET) [Struck, D. K., Hoekstra, D., & Pagano, R. E. (1981) Biochemistry 20, 4093-4099], which allows an accurate quantitation of the fusion process. Evidence is presented indicating that the dilution of the RET probes from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
112
2
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 39 publications
(82 reference statements)
13
112
2
1
Order By: Relevance
“…Stegmann et al (1986Stegmann et al ( , 1987) also found 100~ fusion activity of the X-47 strain towards erythrocyte ghosts and CL or PS liposomes, but only 20 to 45 ~ of the virions fused with PC/PE liposomes with or without disialoganglioside GDla (Stegmann et al, 1985(Stegmann et al, , 1989Nir et al, 1988). Sendal virus also showed complete fusion activity towards erythrocyte ghosts (Hoekstra & Klappe, 1986;Nir et al, 1986b) and cells , but had incomplete fusion activity towards several liposomes, including PS and phosphatidylglycerol (Amselem et al, 1986;Nir et al, 1986c).…”
Section: Discussionmentioning
confidence: 98%
“…Stegmann et al (1986Stegmann et al ( , 1987) also found 100~ fusion activity of the X-47 strain towards erythrocyte ghosts and CL or PS liposomes, but only 20 to 45 ~ of the virions fused with PC/PE liposomes with or without disialoganglioside GDla (Stegmann et al, 1985(Stegmann et al, , 1989Nir et al, 1988). Sendal virus also showed complete fusion activity towards erythrocyte ghosts (Hoekstra & Klappe, 1986;Nir et al, 1986b) and cells , but had incomplete fusion activity towards several liposomes, including PS and phosphatidylglycerol (Amselem et al, 1986;Nir et al, 1986c).…”
Section: Discussionmentioning
confidence: 98%
“…5). Reported values for macroscopic fluorimetrically measured R18 dequenching half-times are also heterogeneous, with some time constants for influenza and other virus types being similar (1,3,17,18), while faster values in the range of 1-10 s have been observed and reported (2). From rates of respiratory syncytial virus budding and readsorption observed by using a differential interference contrast video-microscopy method (7), it was proposed that the fusion rate for an influenza-sized virus would be less than 1 s. In a preliminary description of video microscopy (19,20) monitoring fusion of R18-labeled virus to artificial bilayer membranes it was reported that rapid rates were observed and that influenza virus fusion was faster than Sendai virus fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable insight has been gained recently by studying the fusion of viruses with cell plasma membranes by spectrofluorometric methods (1)(2)(3)(4)(5)(6). Virus particles are labeled with the lipid analogue octadecylrhodamine B (R18), which intercalates in the viral coat at concentrations that cause selfquenching ofthe fluorochrome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ployed the fluorescence resonance energy transfer (FRET)-based virus-liposome fusion assay (18) adapted to a 384-well plate reader format. In this assay, the FRET pair consisting of (N-7-nitrobenz-2-oxa-1,3-diazol-4-yl)-1,2-dihexadecanoyl-sn-glycero-3-phosphatidylethanolamine (NBD-PE; Molecular Probes) and rhodamine-phosphatidylethanolamine (Rh-PE; Avanti) is added to liposomes in quantities that allow transfer of the NBD emission energy to Rh-PE in the liposome.…”
mentioning
confidence: 99%